Hubungan Gaya Kepemimpinan Demokratis Kepala Ruangan dengan Kepuasan Kerja Perawat - Sasteri Yuliyanti; Elvira Eka, Agustina; Sulastri (ProHealth Journal, 2025)
Democratic leadership is a type of leadership that involves the participation of members in the decision-making process to build work commitment in achieving organizational goals. Democratic leadership is one of the factors that can influence nurses' job satisfaction. Aim to determine the relationship between democratic leadership style and nurses' job satisfaction. Method this study used a cross sectional approach with a sample of 80 nurses in inpatient ward at Empat Lawang Hospital, and chosen with total sampling. Data was collected using a questionnaire. Data analysis was performed in univariate and bivariate (chi-square).Result The results of the study were obtained by most of the 57 (71.3%) showed that most respondents assessed the head nurse’s leadership style as high and job satisfaction was categorized as very satisfied (72.5%). The bivariate analysis indicated a significant relationship between democratic leadership style and nurses’ job satisfaction (p= 0.000). Conclusion nurse job satisfaction is significantly influenced by the democratic leadership style of the ward head, so the researcher suggests that the hospital management be more consistent in implementing a democratic leadership style.